Teaching research skills through embedded librarianship. Issue 2 (12th June 2017) - Hoffman, Nadine; Beatty, Susan; Feng, Patrick; Lee, Jennifer
Abstract : Purpose: This pilot aims to study a way of integrating research and writing support into a university course along with content. Research and writing skills are not taught explicitly in most university courses, yet these skills are increasingly required both in and outside of the classroom. Design/methodology/approach: An embedded, collaborative instructional team comprising the instructor, librarians and writing specialists re-designed a first-year inquiry-based learning course, incorporating research and writing instruction throughout, formative and summative assessments and a flipped classroom model. At the end of the course, each member of the team reflected on their collaborative and individual experiences. The team also surveyed students to gauge their perceptions of the research and writing sessions. Findings: The team learned from this experience and noted a large, but rewarding, time commitment. The flipped classroom model allowed the tailoring of instruction to students' needs but required more work by librarians to prepare content and to grade. Students indicated appreciation for repeated interactions with librarians and reported confidence to use the skills taught. Originality/value: Embedding librarians throughout the course with a writing specialist, as well as involvement in grading, is novel – this may be the first example in the literature of "deep integration". The concept of "embedded librarianship" can be enhanced by expanding librarian and other support roles in a course.